Training on Oxytocin Hormone Stimulation for Family Assistance Cadres of Traditional Health Services Program (YanKesTrad) in Blang Mangat Community Health Center Area, Lhokseumawe City - Nurdahliana, Nurdahliana; Sukmadewi, Meliani; Marlina, Marlina; Henniwati, Henniwati (Journal of Community Service and Society Empowerment, 2025)
This community service program aimed to improve the knowledge and practical skills of family assistance cadres on Oxytocin Hormone Stimulation (OHS) within the Traditional Health Services Program (Yankestrad) in the Blang Mangat Health Center area, Lhokseumawe City. Conducted from May 18 to May 21, 2024, the training involved 26 cadres and utilized a combination of educational, participatory, and hands-on approaches. The implementation was divided into several key phases: preparation, training execution, immediate and follow-up evaluation, and report compilation. Educational sessions included structured lectures, demonstrations of oxytocin massage techniques, and supervised hands-on practice based on standard operating procedures (SOP). A pre-test and post-test assessment design was employed to measure the knowledge improvement. The results indicated a significant increase in participants' knowledge. Prior to the training, 50% of the cadres scored in the "fair" category and 50% in the "poor" category. Following the training, 88.5% reached the "fair" level and 11.5% advanced to the "good" level, with no participants remaining in the "poor" category. These results, supported by SPSS analysis, reflect the effectiveness of the intervention in addressing knowledge gaps and equipping cadres with the competencies to support breastfeeding mothers through oxytocin stimulation techniques. The strong institutional collaboration with the Blang Mangat Health Center and Sub-District Office was instrumental in the successful implementation of the program